Lentinula edodes extract as the source of β-glucans and its potential as lip balm’s additive / Shafinas Abdullah … [et al.] - Abdullah, Shafinas; Abdul Hadi, Nurul Fakhira; Zainuddin, Nur Jannah; Alias, Nurul Zawani; Md Amin, Mohamad Afiq (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Lentinula edodes has been acknowledged as a well-known cultivated edible and medicinal fungi due to its nutritional and therapeutic characteristics such as good antioxidant properties. However, it is susceptible to postharvest problems such as gill browning, fruiting body softening, and lentinan degradation that will reduce its nutrition availability. This study was conducted to extract β-glucans from Lentinula edodes, examined the antioxidant activity as well as its potential as lip balm’s additive. In this study, the β-glucans from Lentinula edodes was extracted using Soxhlet extraction and further characterized by using FTIR and phytochemical screening analysis. Based on the FTIR result, the predominant functional groups in the extracted Lentinula edodes were at 879 cm-1 for C-H β-glycosidic linkage and 1196 cm-1 for C-O (ether) of glycosidic linkage which are comparable with the functional group of β-glucans stated in the previous study. The preliminary phytochemical study findings are consistent with the published studies of extracted Lentinula edodes which contained alkaloid, phytosterol, gum, mucilage, flavonoid and tannins. Besides, β-glucans extracted from Lentinula edodes was found to possess good antioxidant activity (27.9962 µg/mL). The prepared lip balm, demonstrates consistent spread ability under a variety of settings and has a pH of 6.5, making it safe to be used on the lips. The results of this study inferred that Lentinula edodes has great potential to be used as a polymeric excipient for health supplement, food additives with antioxidant as well as suitable to be commercialized in cosmeceutical industry, which can contribute to enhance health and beauty.